2008
DOI: 10.1080/13561820701714763
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional ambulatory primary care practice-based educational program

Abstract: Although interprofessional teamwork and collaboration are considered key elements for improving patient outcomes, there are few reports of controlled studies involving interprofessional training of health care learners in the ambulatory primary care setting. We describe an educational program for teams of nurse practitioners, family medicine residents and social work students to work together at clinical sites in the delivery of longitudinal care in primary care ambulatory clinics. Year 1 was a planning year. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 10 publications
1
26
0
Order By: Relevance
“…Some studies already reported the benefits of IPE on choice of employment (Norris, House, Schaad, Mas, & Kelday, 2003;Rhyne, Daniels, Skipper, Sanders, & Vanleit, 2006), cost benefits (Hansen, Jacobsen, & Larsen, 2009) and changes in attitude for CP (Anderson, Thorpe, Heney, & Petersen, 2009;Coleman, Roberts, Wulff, Van Zyl, & Newton, 2008;Gursoy, Ocek, Ciceklioglu, Aksu, & Soyer, 2008). These studies can help policy makers understand the importance of IPE in the academic setting.…”
Section: Discussionmentioning
confidence: 90%
“…Some studies already reported the benefits of IPE on choice of employment (Norris, House, Schaad, Mas, & Kelday, 2003;Rhyne, Daniels, Skipper, Sanders, & Vanleit, 2006), cost benefits (Hansen, Jacobsen, & Larsen, 2009) and changes in attitude for CP (Anderson, Thorpe, Heney, & Petersen, 2009;Coleman, Roberts, Wulff, Van Zyl, & Newton, 2008;Gursoy, Ocek, Ciceklioglu, Aksu, & Soyer, 2008). These studies can help policy makers understand the importance of IPE in the academic setting.…”
Section: Discussionmentioning
confidence: 90%
“…Interprofessional education is necessary to prepare students in the health care professions with competencies for working collaboratively to provide comprehensive services for older adults (Coleman, Roberts, Wulff, Zyl, & Newton, 2008;WHO, 2010).…”
mentioning
confidence: 99%
“…Improvement in professional skills such as communication and empathy were reported in studies such as those by Snadden and Mowat (1995), Howe (2001) and Seifer (2000). A third common outcome area is promotion of teamwork and appreciation of the importance of an interprofessional approach to health; examples of studies reporting such outcomes include Goswami et al (1998), Dornan et al (2006) and Coleman et al (2008).…”
Section: Practice Pointsmentioning
confidence: 92%